Understanding The Implementation Of Economic Value Added (Eva™) In China Construction Bank (Ccb): Utilizing The Institutional Work Perspective - Lina, Song (2024)
This thesis investigates the implementation of Economic Value Added (EVA™) within China Construction Bank (CCB) Inner Mongolia provincial branch, utilizing the institutional work framework developed by Perkmann and Spicer (2008) and Lawrence and Suddaby (2006). This branch was one of the early adopters of EVA™ in a region characterized by a distinct socio-economic and cultural landscape. Specifically, the study identifies three phases of institutionalization: initial adoption driven by competitive pressures and regulatory changes, early institutionalization, and continued institutionalization despite ongoing challenges and mixed outcomes. Through a qualitative interpretive case study, data were gathered from interviews, observations, and document analysis to provide a comprehensive understanding of how EVA™ became ingrained in CCB’s practices. The research critically examines the specific political, technical, and cultural work that facilitated the implementation of EVA™ within CCB, while also evaluating the interplay among these works in institutionalizing the practice. This study further explores the underlying reasons for the institutionalization of EVA™ within CCB, even amid recognized shortcomings and criticisms. Theoretically, this study introduces the Multidimensional Institutional Work (MIW) framework, integrating political, technical, and cultural work while emphasizing the importance of their synchronization. It highlights the concept of accumulative partaking, showcasing how decentralized efforts drive institutional change.